STRATEGI BRANDING HOTEL DALAM MEMBENTUK PERSEPSI WISATAWAN RUSIA DAN MINAT KEMITRAAN TRAVEL AGENT - Hapsari, Diva Zahra (Sintesa, 2026)
This study aims to determine how the consistent branding strategy of Hotel Ibis Styles Ao Nang Krabi is able to shape positive perceptions among Russian tourists and how these perceptions relate to travel agents’ interest in partnership. This research uses a qualitative approach with descriptive type. Data collection techniques include in-depth interviews, participatory observations, and documentation from promotional media and guest reviews on digital platforms. The results of the study show that consistent branding in visual elements, communication style, and hotel service succeeds in creating a professional image that Russian tourists trust. This strengthens their decision to choose a hotel and recommend it. In addition, travel agents find it helpful because the hotel already has a strong brand identity and promotional materials that are ready to be used. Stable branding facilitates the process of cooperation and the preparation of attractive tour packages for foreign tourists, especially from Russia. These findings show that hotel branding not only shapes guest perception, but also becomes an important part of marketing and distribution communication strategies. This research provides practical insights for hotel managers and Communication Science students in understanding the role of brand communication in the hospitality industry. Keywords: Communication Strategy, Hospitality Industry, Hotel Branding, Russian Travelers, Travel Agent.